An empirical investigation of fiscal policy in New Zealand - Iris Claus; Aaron Gill; Boram Lee; Nathan McLellan (New Zealand Government, The Treasury, 2006)
This paper examines the effects of fiscal policy, measured by changes in government spending and net tax (government tax revenue less transfer payments), on New Zealand GDP. The framework of analysis is a structural vector autoregression (VAR) model of the New Zealand economy, employing and extending estimation techniques used by Blanchard and Perotti (2002). This model is then used to examine the dynamic effects of changes in government spending, taxes and transfers on GDP and the contributions of discretionary fiscal policy to New Zealand business cycles.
Keywords: C32; E32; E62; 330; Fiscal policy; business cycle fluctuations; vector autoregression